Performance study of Non-descript, Hilly and Naked Neck indigenous chicken at fifth generation (Bangladesh Journal of Livestock Research, 2020)
The present study was conducted at Bangladesh Livestock Research Institute, Savar, Dhaka to assess the performances of three Indigenous Chicken genotypes under intensive management. A total of 1128-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Deshi (ND) were hatched in one batch for this study. Significant (p